ADSORTION ISOTHERM OF LEAD ON CALCIUM CARBONATE - & et al., Al-Hassoon (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study investigate the effect of concentration of lead ions (Pb2+) at 0,1, 2, 3, 4, 5, 10,20,30, 40,50 and 100 mg L-1, concentrations of the quantity of the adsorbed Pb on surface of calcium carbonate at a temperature of 298° Kelvin with all other variables remained constant, was carried out and this experiment was conducted in a single batch and using lead nitrate solution . The results showed that quantity of the adsorbed lead increased from 2.6 to 1924 mg kg-1 Calcium carbonate, and when single and two surface  Langmuir, Freundlich, Temkin, Dubinin and Polani equations were applied, they were able to describe lead adsorption on the surface of calcium carbonate at the used concentrations. The two surface Langmuir equation was  most efficient in used mathematical description of  lead adsorption, and the bonding energy (K) with the first and second surfaces were  4.02 and 1613.42 L mg-1 respectively. The adsorption capacity (Xm) values with the first and second surfaces were 0.25 and 0.89 mg    kg -1 respectively , and this clearly indicated to high capacity of the second surface (carbonate surface) to adsorb lead.